Cephalometric Evaluation of Nasopharyngeal Airway and Hyoid Bone Position in Subgroups of Class II Malocclusions - Buyukcavus, Muhammed Hilmi (2020)
The aim of the study is to evaluate pharyngeal airway dimensions and hyoid bone position according to different Class II malocclusion types in Turkish population. Materials and Methods: The retrospective clinical study consisted of patients divided into 3 subgroups with skeletal Class II malocclusion. A total of 221 individuals (131 females and 90 males) were included in the study. Individuals with skeletal Class II malocclusion were divided into three subgroups as maxillary prognathia, mandibular retrognathia and combined. In the cephalometric analysis; 8 nasopharyngeal, 7 oropharyngeal, 2 hypopharyngeal, 9 hyoid measurements and 4 area measurements were used. The distribution of sex and growth-development stages of the patients were compared with the Pearson chi-square test. One-way ANOVA was used to evaluate patients. Tukey Post-Hoc tests were used for bilateral comparisons for significant parameters. SPSS package program was used for data analysis. Results were considered statistically significant at p<0.05 significance level. Results: According to findings, there was no significant difference between the groups in nasopharyngeal airway and area measurements (p>0.05). When the position of the hyoid bone was evaluated, a statistically significant difference was found between the three groups in the measurements of Hy-Pg (mm) (p<0.05). Conclusion: Linear and areal nasopharyngeal airway dimensions are similar in subgroups of Class II malocclusions, while the distance of the hyoid bone from the pogonion is less in the mandibular retrognathia group.